Penyusunan Anggaran Bagi Usaha Kecil dan Menengah Di Kota Bandar Lampung - Arie Sarjono Idris; Nety Kumalasari; Desmon Desmon; Dwi Fitriyani (Institut Teknologi dan Bisnis Semarang, 2023)
Community service activities to provide knowledge about Budgeting for Small and Medium Enterprises in the City of Bandar Lampung. activity methods with workshop presentations, discussions and exercises for making budget reports. The series of community service activities is as follows: the implementation team presents material on making budget reports consisting of a sales budget and cash budget, the Service Team asks for participant feedback regarding the quality of the training including understanding of the material, activity benefits and satisfaction with activity implementation, based on the feedback provided Community service activities have a good impact on participants where participants can better understand budgeting.